EFEKTIVITAS PERMAINAN EDUKATIF BERBASIS JEOPARDY DALAM MENDUKUNG PROSES PEMBELAJARAN: KAJIAN LITERATUR - Sapna, Airin; Fadilah, Muhyiatul; Yogica, Relsas; Rahmi, Fitri Olvia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Effective learning requires strategies that enhance student engagement in the learning process. One innovation that can be implemented is a Jeopardy-based educational game. This study aims to examine the effectiveness of Jeopardy-based educational games in supporting the learning process. The method employed was a literature review using a Systematic Literature Review approach on five articles published in national journals within the last five years. The results indicate that Jeopardy Games positively contribute to the learning process by improving learning motivation, student activeness, engagement, and learning outcomes. It can be concluded that Jeopardy-based educational games are an effective instructional innovation with potential for implementation across various educational levels and subject areas.